(untitled) (Scientific journal of the Fergana State University, 2026)
This article presents an overview of metonymy as both a general linguistic notion and a discursive phenomenon. The concept of “discourse” is briefly examined through the ideas of linguists who have contributed to its understanding. Some key features of metonymy are defined and illustrated with relevant examples, and its relationship with discourse is discussed in a concise manner.